Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1289/ehp.8353163
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of asbestos genotoxicity.

Abstract: Asbestos fibers are highly cytotoxic to cultured mammalian cells and produce chromosomal aberrations in several rodent cell types. There is some uncertainty in the literature as to whether these fibers are clastogenic to cultured human cells. Asbestos fibers do not produce either DNA damage or back mutations in prokaryotic assay systems, and they do not appear to cause DNA strand breaks in either rodent or human cells. The evidence that these fibers can produce either forward mutation or neoplastic transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…There is evidence to suggest that the array of DNA and chromosomal damages induced by ROS such as base substitutions, deletions, rearrangements, insertions, sister chromatid exchanges, and chromosomal aberrations may lead to a broad spectrum of mutations in mammalian cells (16). However, earlier studies on the mutagenicity of asbestos at either the hprt or oua loci in a variety of mammalian cells have resulted in mostly negative findings (17,18). Subsequent studies have suggested that this could be a result of multilocus deletions induced predominantly by asbestos, which are not compatible with the survival of the mutants.…”
mentioning
confidence: 99%
“…There is evidence to suggest that the array of DNA and chromosomal damages induced by ROS such as base substitutions, deletions, rearrangements, insertions, sister chromatid exchanges, and chromosomal aberrations may lead to a broad spectrum of mutations in mammalian cells (16). However, earlier studies on the mutagenicity of asbestos at either the hprt or oua loci in a variety of mammalian cells have resulted in mostly negative findings (17,18). Subsequent studies have suggested that this could be a result of multilocus deletions induced predominantly by asbestos, which are not compatible with the survival of the mutants.…”
mentioning
confidence: 99%
“…For example, various types of asbestos do not cause single-strand breakage of DNA (30) and are not mutagenic in a number of cell types (22). A number of experimental and epidemiologic studies support this observation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, critical cellular levels of polyamines must exist for cell division to occur. (30) and are not mutagenic in a number of cell types (22). Moreover, asbestos, unless combined with PAH, is not carcinogenic in hamster tracheal implants (36,37) and is only weakly carcinogenic in rats after repeated intratracheal instillations (23).…”
Section: Stimulation Of Ornithine Decarboxylase (Odc) By Asbestosmentioning
confidence: 99%
“…An initiator is defined as an agent interacting directly with the DNA of a cell, whereas a promoter influences the establishment and develoment of a tumor. As discussed by Daniel in these proceedings (22), the evidence implicating asbestos as a mutagenic agent in intestinal and other cell types is weak; thus its role as an initiator of carcinogenesis is questionable. On the other hand, work from our laboratory shows that the properties of asbestos in cell and organ cultures of trachea are similar to classical tumor promoters such as phorbol esters (23,24).…”
Section: Initiation and Promotionmentioning
confidence: 99%